The law applicable to copyright infringement on the Internet - Torremans, Paul (T.M.C. Asser Press / Springer, 2016)
This article looks at the law applicable to copyright infringement on the Internet. In order to do so we need to look first of all at the rules concerning the applicable law for copyright infringement in general. Here the starting point is the Berne Convention. Its provisions give an indication of the direction in which this debate is going, but we will see that they merely provide starting points. We then move on to the approach in Europe under the Rome II Regulation and here more details become clear. Essentially, the existing rule boils down to a lex loci protectionis approach, which is in conformity with the starting point that is found in the Berne Convention. It is however doubtful whether such a country by country approach can work well in an Internet context and suggestions are made to improve the legal framework by adding a rule for ubiquitous infringement and a de minimis rule. Finally, we also briefly look at the issues surrounding the cross-border portability of online content services and the impact that the current focus on these may have in terms of the choice of law.